Suspicion of Duchenne Muscular Dystrophy in A 7-Year-Old Madurese Boy: A Rare Case Report - Suci Rizalah Islamiyah; Garata Dwi Yulia Nurul Putri (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Duchenne Muscular Dystrophy (DMD) is an X-linked disorder presenting in early childhood and characterized by proximal muscle weakness and calf hypertrophy in affected boys associated with a functional deficiency of dystrophin. The incidence of these cases reached 1 in 3500-6000 male births. Research at RSUPN Dr Cipto Mangunkusumo (RSCM) showed that DMD is the second most frequent neuromuscular disorder in children regardless there is no prevalence data available yet in Indonesia. It is quite complicated to diagnose DMD due to the limited facilities of genetic testing and its high cost. Case Presentation: A 7-year-old boy came with the main complaint of weakness in both legs progressively two years before admission. He had to hold onto the floor and then both knees when started to stand. There was a history of motor and speech delay but family history was denied. Vital signs and nutritional status were within normal. Laboratory examination revealed significantly elevated levels of CK, ALT, and AST. The EMG result supported the presence of myopathy. Due to a lack of facilities, genetic testing or muscle biopsy could not be done. He received prednisone once a day with a 14 mg dose and was scheduled to attend regular physiotherapy. Conclusion: In a limited facilities area, the clinician should have a suspicion of DMD not only by anamnesis and clinical features, but also by considering the elevated levels of CK and myopathies on EMG.